Five‐fold‐symmetric Pentabromo‐ and Pentaiodo‐corannulenes: Useful Precursors of Heteroatom‐substituted Corannulenes. Issue 3 (22nd January 2021) - Kise, Koki; Ooi, Shota; Osuka, Atsuhiro; Tanaka, Takayuki
Abstract: Five‐fold‐symmetric pentabromo‐ and pentaiodo‐corannulenes were synthesized in sub‐gram scale in high yields under aerial conditions and were purified without any chromatographic separations. The obtained pentahalocorannulenes were fully characterized by NMR, MS, and X‐ray crystallography. The pentahalocorannulenes are useful precursors of five‐fold symmetric heteroatom‐substituted corannulenes that are difficult‐to‐address from known corannulene derivatives. As a representative example, pentaphosphinylated corannulene was prepared for the first time and was comprehensively characterized. Abstract : Five‐fold‐symmetric pentabromo‐ and pentaiodo‐corannulenes were synthesized in 77–80% yields in sub‐gram scale under aerial conditions. The obtained sym ‐pentahalocorannulenes serve as pivotal precursors of five‐fold‐symmetric substituted corannulene. As a demonstration, sym ‐pentaphosphinylated corannulene was prepared for the first time from sym ‐pentaiodocorannuelne or sym ‐pentabromocorannulene in up to 82% yield.